Implikasi Hiperinflasi Republik Bolivar Venezuela Terhadap Regionalisme Amerika Latin - Dwi Rizki Woelandari; Devi Amelia Kartika; Retno Riyanti Sastro Amijoyo (Proyeksi: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2022)
This article aims to explain the hyperinflation phenomenon in Venezuela and the policy stance taken by Venezuela under the pressure of the economic crisis and domestic problems that occurred in the country. And how big are the implications resulting from hyperinflation that occurred in Venezuela for countries in the Latin American region in terms of trade and finance in the face of hyperinflation that is developing in the Latin American regional and international scope. This study uses the theory of constructivism and regionalism by using a qualitative descriptive approach which is carried out by collecting data from books, writings, articles, journals, and the authors also seek data and information relevant to this research from electronic media with reliable sources, so that research accuracy can be achieved.